Correlation between APACHE II Score and Mortality Rate in PKU Gamping Hospital ICU patients - Yosy Budi Setiawan; Dito Mahardika Prambudi (Pelopor Publikasi Akademika, 2023)
The intensive care system have a duty to help patients in healing process and not to delay patient’s death. Therefore many scoring methods was developed to predict the outcome of care and mortality rate in the ICU. One of those methods is APACHE II that scores 12 physiological variables and pre-existing conditions in the patients. This research was done to find the correlation between APACHE II score and mortality rate of PKU Gamping hospital ICU patients. The data used medical records for 61 non-operative patients from June-December 2019. This research found that 37 (60.6%) died and 24 (39.4%) lived after treatment. The average APACHE II score was 21.28 with the lowest score of 3 and the highest score of 43, after the data gathering a correlation test was conducted using Spearman-correlation test. In the data analysis p value of 0.000 (p<0.05) and correlation coefficient of .698 was found. there was a significant correlation between the APACHE II score and the mortality rate of the PKU Gamping hospital ICU patients, where with higher number of score there was higher number of patient’s death.